Developing novel innate immunity assays for the investigation of primary immune deficiencies. (29th September 2015) - Klaber, E; Chouwdhury, F; Chowdhury, Y; Ramakrishnan, KA; Doffinger, R; Kumaratne, D; Faust, S; Williams, A
Abstract : Aims: (1) To develop a single-tube assay to identify immune responses of NK-cells, monocytes and dendritic cells following toll-like ligand induced activation in whole blood. (2) To evaluate Th1 responses in the context of toll-like ligand and mitogen induced activation in whole blood. (3) To investigate our index patient, 4-year-old male, who presented with a history of BCGosis, mucocutaneous candidiasis and bronchiectasis (REC 09/H0502/4). Methods: Multiparametric flow cytometry was utilised to evaluate whole blood responses using small sample volumes (500 mcl). Activating ligands include lipopolysaccharide (TLR4 ligand) and lipoteichoic acid (TLR 1+2 ligand). Phytohaemagluttinin was used as a mitogen for T cell activation. Cytometry panels were constructed to identify monocytes (CD14), plasmacytoid DCs (BDCA-2) myeloid DCs (BDCA-1) in conjunction with the intracellular cytokines tumour necrosis factor α (TNFα) and interferon γ (IFNγ). Cells were activated for 6 h in the presence or absence of brefeldin A (BFA) to identify activated cells. Supernatants collected in the absence of BFA were analysed by Luminex(R) cytokine capture assay. Dendritic cells were assessed for activation using the cell surface markers CD83 and CCR7. Results: Assay: initial experiments established that over 90% of monocytes respond to LPS with the production of TNFa. Index patient: parallel evaluation flow cytometry and Luminex(R) demonstrated normal LPS responsiveness. Th1 profiling showed no increase in IFNg production post PHA by intracellular staining and supernatant quantitation, which could not be corrected with exogenous IL-12. Conclusion: The development of new tools to evaluate host immune responses provides the opportunity to understand in greater detail defects not identified within current diagnostic investigations. The authors have established a small sample volume technique that is able to provide an in-depth evaluation of TLR responses. Initial results in the index patient suggest that there is an intact Toll-like ligand axis but a defect in Th1 immunity. Future work will consider novel defects in the development of Th1 immunity assessing the differentiation of naïve cells to Th1 in vitro and the activity of Th1 transcription factors.